To engage or not? Antecedents of employee engagement in Sri Lanka - Mayuran, L.; Kailasapathy, P. (Wiley Online, 2020)
This study integrates the resource demand and social exchange perspectives and assesses if employer brand, organizational politics, self-efficacy, and family-work conflict predict employee engagement. Furthermore, this paper examines the impact of boundary conditions of employee engagement by focusing on exchange ideology and gender. Data were collected using questionnaires from 411 managerial employees working in licensed commercial banks in Sri Lanka. The results revealed that employer brand, perceived organizational politics, and self-efficacy were significantly related to employee engagement. The results, however, did not support the negative relationship between family-work conflict and employee engagement or the moderating effect of gender on the relationship between family-work conflict and employee engagement. But, exchange ideology moderated the relationship between employer brand and employee engagement albeit contrary to the hypothesized directions. The implications of this research, possible limitations and directions for future research are also discussed.
Keywords: Employee engagement; Employer brand; Family-work conflict; perceived organizational politic; self-efficacy